Examining the intention to cruise again sooner rather than later. (December 2016) - Mahadevan, Renuka
This article identifies temporal differences in the factors that influence a cruise passenger's intention to cruise again in the short-, medium- and long-term. Using a sample of Australian cruisers, the reputation of a cruise line and indulging in interesting and different ship activities are found to be weakly influential, while satisfaction from past cruises and educational cruises are important factors in the choice to cruise again in the short-term. But variety in ports of call and cruise destinations, recent frequent past trips and recommended cruises influence cruising again in the medium-term. While first-time cruisers are not likely to cruise again in the short-term, neither are those looking for a sense of exoticism and adventure, and wanting to go to places not accessible by land. These findings have implications for the effective targeting of marketing and advertising, keeping in mind the time frame of the likely intentions to cruise again.